Effect of Corporate Social Responsibility and Firm Life Cycle on Banking Performace in Indonesia - Inas Yusriyyah Zain (Universitas Negeri Padang, 2022)
The study aims to analyze the effect of (1) of Corporate Social Responsibility on banking performance, (2) Firm life cycle on banking performance and (3) Corporate Social Responsibility on every firm life cycle with banking performance proxies listed on the Indonesia Stock Exchange in 2018-2020. The study used two control variables: firm size and economic condition. The population in this study is all banking companies listed on the Indonesia Stock Exchange. While the samples in the study were determined by the purposive sampling method, the banking company's samples for three consecutive years from 2018-2020, resulting in a samples count of 34 companies with 93 observations for each variable. The analysis method used is multiple linear regression analysis using the IBM SPSS Statistics 26 program. The results of this study concluded that (1) Corporate Social Responsibility using GRI standard has no significant effect on banking performance proxies, (2) Firm life cycle with RETE ratio has a significant effect on banking performance proxies, (3) Firm life cycle can not moderate the influence of CSR on the banking performance